Penerapan Prinsip Permakultur Pada Perancangan Pusat Florikultura Di Pekanbaru - Pratama, Lissya; Husaini, Muhd. Arief Al; Rijal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Currently, floriculture is a significant agribusiness commodity in Indonesia, especially in Pekanbaru. Floriculture is enjoyed in the form of its beauty, therefore the demands for quality are very high. Cultivating various types of floriculture can be a very prospective agribusiness business for today's society. The lack of public awareness of the importance of a fresh environment can affect the increasing demand for floriculture crops, especially during the Covid-19 Pandemic, some people in Pekanbaru recently chose to increase their busyness by planting floriculture. So a Floriculture Center was designed in Pekanbaru, where Pekanbaru is a suitable location for the breeding of floriculture plants which generally have a tropical climate. The design object is integrated with the application of the Permaculture Principles. A theme that holds true to the principles of balance and sustainability. Thus, the Floriculture Center is a center that accommodates facilities in the form of educational and recreational facilities related to the cultivation and development of Floricultural plants. So as to create an architectural container that synergizes with nature and the people in Pekanbaru. Keywords: Florikultura, Pekanbaru, Permaculture Principles